Student STEM Literacy Ability Profile on Environmental Change Issues - Syifa Nurifa Dewi; Kusnadi; Yanti Hamdiyati (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
In addressing environmental issues, it is important to measure STEM literacy achievement to increase students' environmental awareness and equip them with the necessary skills to contribute to finding solutions. This research aims to determine the profile of students' STEM literacy achievement in Bandung regarding environmental change issues. The research method used is descriptive with a qualitative approach. The research subjects comprised 193 tenth-grade students selected from SMA Negeri 1 Bandung, SMA Negeri 4 Bandung, and SMA Negeri 9 Bandung for the 2023/2024 academic year, chosen through simple random sampling. The research instrument consisted of 40 multiple-choice questions on environmental change issues, covering seven STEM literacy indicators: explaining phenomena scientifically, evaluating and designing scientific investigations, interpreting data and evidence scientifically, understanding technological principles, developing solutions to achieve goals, formulating situations mathematically, and using concepts, facts, procedures, or reasoning. Data analysis was conducted by calculating the average score of students' STEM literacy achievement per indicator as a percentage. The research results indicate that the percentage of students' STEM literacy achievement is 70%, categorized as moderate. The percentages per STEM literacy indicator are as follows: explaining phenomena scientifically at 71%, evaluating and designing scientific investigations at 61%, interpreting data and evidence scientifically at 73%, understanding technological principles at 76%, developing solutions to achieve goals at 74%, formulating situations mathematically at 61%, and using concepts, facts, procedures, or reasoning at 61%.